High-Output (HO) Ostomy With Histopathologic Abnormality: Examination of 78 Stoma Specimens. (11th September 2019) - Cordeiro-Rudnisky, Fernanda; Sheuka, Natallia; Lee, Edward; Lee, Hwajeong
Abstract: Background: HO (>2, 000 mL output/day) is a serious complication following ostomy procedure. HO may be associated with variable underlying conditions or idiopathic. We encountered an ileostomy case with diffuse subepithelial collagen deposits resembling collagenous colitis from a patient with history of HO without underlying cause. A subset of idiopathic HO may be associated with histopathologic abnormalities of the bowel. Methods: Resected stomas from ostomy malfunction were searched using ICD-9 and CPT codes (2003-2018). Archived pathology materials were reviewed and activity, villous blunting, pyloric metaplasia (PM), and subepithelial collagen deposits were assessed. Trichrome stain was performed when necessary. Clinical history was obtained from medical records. Results: Sixty-one ileostomies and 17 colostomies were retrieved from 69 patients. Types of ostomy malfunction were stricture/obstruction (n = 21), hernia (n = 10), ischemia/necrosis (n = 4), leak (n = 4), abscess/adhesion (n = 3), skin breakdown (n = 3), prolapse (n = 3), retraction (n = 2), reepithelialization (n = 1), and unclear/not specified (n = 15). Thirty-two patients had inflammatory bowel disease (IBD; 19 Crohn disease [CD], 13 ulcerative colitis [UC]). All HOs were from ileostomy, and 16 had risk factors for HO, including IBD (n = 9 [56%]; 7 CD, 2 UC), short bowel (n = 6, 3 with CD), pelvic/intra-abdominal abscess (n = 2), sepsis (n = 2), and prokinetic (n = 1). Five ileostomies from CD showed PM, while 11 lacked significant histologic abnormalities. Among 5 (24%) idiopathic HOs, 1 was the index case with diffuse subepithelial collagen deposits with subtotal villous blunting, 1 showed PM, and 1 had focal activity. Remaining 2 ileostomies from idiopathic HO were unremarkable. Stomas from patients with other types of ostomy malfunction showed compatible histologic changes. Fifteen cases without ostomy malfunction did not show histologic abnormality. Conclusion: Most HO represents functional abnormality without histopathologic abnormality except in IBD. However, idiopathic HO may be associated with histopathologic abnormalities in the stoma suggestive of acute/chronic enteritis and scarring, which may be underrecognized and treatable.